Multiple Acquisitions of Pathogen-Derived Francisella Endosymbionts in Soft Ticks. (29th January 2018) - Gerhart, Jonathan G; Auguste Dutcher, H; Brenner, Amanda E; Moses, Abraham S; Grubhoffer, Libor; Raghavan, Rahul
Abstract: Bacterial endosymbionts of ticks are of interest due to their close evolutionary relationships with tick-vectored pathogens. For instance, whereas many ticks contain Francisella -like endosymbionts (FLEs), others transmit the mammalian pathogen Francisella tularensis . We recently sequenced the genome of an FLE present in the hard tick Amblyomma maculatum (FLE-Am) and showed that it likely evolved from a pathogenic ancestor. In order to expand our understanding of FLEs, in the current study we sequenced the genome of an FLE in the soft tick Ornithodoros moubata and compared it to the genomes of FLE-Am, Francisella persica —an FLE in the soft tick Argus (Persicargas) arboreus, Francisella sp. MA067296—a clinical isolate responsible for an opportunistic human infection, and F. tularensis, the established human pathogen. We determined that FLEs and MA067296 belonged to a sister taxon of mammalian pathogens, and contained inactivated versions of virulence genes present in F. tularensis, indicating that the most recent common ancestor shared by FLEs and F. tularensis was a potential mammalian pathogen. Our analyses also revealed that the two soft ticks ( O. moubata and A. arboreus ) probably acquired their FLEs separately, suggesting that the virulence attenuation observed in FLEs are not the consequence of a single acquisition event followed by speciation, but probably due to independent transitions of pathogenic francisellae into nonpathogenic FLEs within separate tick lineages. Additionally, we show that FLEs encode intact pathways for the production of several B vitamins and cofactors, denoting that they could function as nutrient-provisioning endosymbionts in ticks.